PERBANDINGAN LAPORAN PERUBAHAN EKUITAS SEBELUM DAN SESUDAH PENERAPAN IFRS SERTA PENGARUHNYA TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Feprida, Linda Andria (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
International Financial Reporting Standards (IFRS) is the international accounting standards issued by the International Accounting Standards Board (IASB). Statement of Changes in Equity is a financial statement that shows the change in equity during a given period. This study aims to analyze and test the statement of changes in equity differences before and after the application of IFRS as well as to examine the effect of changes in equity on stock return. The samples are companies listed on the Indonesia Stock Exchange for four years i.e 2008-2011. The sampling technique using purposive sampling, number of samples used 16 companies of 132 manufacturing companies. This research uses explanation. Analysis by using Simple Linear Regression Analysis and hypothesis testing use t-test (different) or paired sample test. The analysis showed that there are significant between the statements of changes in equity on stock returns. T test (different) showed that there is a difference between the statement of changes in equity before and after the implementation of IFRS. This study is expected to be a reference for researchers who want to conduct further research on the comparative statement of changes in equity before and after implementation of IFRS (International Financial Reporting Standards), as well as being interested in solving the problem of the influence of changes in equity on stock returns. Thus, this study can be continued by adding more variables and using a longer study period in accordance with the company to be sampled, so get more relevant results.